Bis(methylborole) sandwich compounds of the first row transition metals. (24th November 2015) - Chen, Jianlin; Feng, Hao; Xie, Yaoming; King, R. Bruce
Graphical abstract: The late transition metal derivatives (η 5 -C4 H4 BCH3 )2 M (M = Ni, Co, Fe, Mn, and Cr) energetically prefer sandwich structures having parallel pentahapto borole rings. However, the early transition metal (η 5 -C4 H4 BCH3 )2 M derivatives (M = Ti, V, Cr) energetically prefer bent sandwich structures having ∼30° dihedral angles between the pentahapto borole rings. Abstract: Bis(borole)nickel derivatives (η 5 -C4 H4 BR)2 Ni, isoelectronic with the corresponding ferrocenes (η 5 -C5 H4 R)2 Fe, have been synthesized and characterized structurally by X-ray crystallography as sandwich compounds with parallel borole rings. The geometries, energetics, and preferred spin states of the complete series of bis(methylborole)metal sandwich compounds (C4 H4 BCH3 )2 M of the first row transition metals (M = Ti to Ni) have now been investigated by density functional theory. The late transition metal derivatives (η 5 -C4 H4 BCH3 )2 M energetically prefer metallocene-like sandwich structures having parallel pentahapto borole rings with singlet, doublet, triplet, quartet, and quintet spin states for M = Ni, Co, Fe, Mn, and Cr, respectively. However, the early transition metal (η 5 -C4 H4 BCH3 )2 M derivatives energetically prefer bent sandwich structures having ∼30° dihedral angles between the pentahapto borole rings with singlet, doublet, and triplet spin states for M = Ti, V, and Cr, respectively. For (η 5 -C4 H4 BCH3 )2 Cr the closeness in energy (within ∼1 kcal/mol) of the parallel quintet and bent triplet structures suggests interesting magnetic properties. The titanium and vanadium derivatives are predicted to form marginally stable [(C4 H4 BCH3 )2 M]2 dimers (M = Ti, V) with the two halves linked by a metal–metal bond as well as two bridging borole carbon atoms through agostic hydrogen atoms.